Optimization of red algae (Kappaphycus alvarezii) lozenges: formulation design and antioxidant evaluation - Putriana Rachmawati; Brian Tinanto; Mathias Lourdion Kusnaman; Pretty Falena Atmanda Kambira (Faculty of Pharmacy, Universitas Pancasila, 2026)
Red algae (Kappaphycus alvarezii) are a marine resource containing bioactive compounds, such as flavonoids and carotenoids, with potential antioxidant properties. This study aimed to develop lozenge formulations of red algae powder using direct compression, optimize the excipient composition, and evaluate the physicochemical properties and antioxidant activity. Red algae powder was characterized microscopically and by LC–MS, confirming the presence of quercetin, rutin, kaempferol, and astaxanthin in the powder. Five lozenge formulations (F1–F5) were prepared using varying concentrations of hydroxypropyl methylcellulose (HPMC) and starch. In-process evaluation included flow rate, angle of repose, loss on drying, and particle size distribution, while post-compression testing covered organoleptic properties, weight variation, hardness, friability, surface abrasion, and disintegration time. Antioxidant activity was determined using the DPPH radical scavenging assay, with quercetin as the standard. All formulations met the pharmacopeia standards, with hardness ranging from 74.3–111.1 N, friability 0.61–0.98%, and disintegration times 6.61–15.88 min. Optimization using a Simplex Lattice Design identified Formula 3 (3.5% HPMC and 10.5% starch) as the most desirable composition. The red algae powder and lozenge exhibited weak antioxidant activity, with IC₅₀ values of 5,969 ppm and 6,854 ppm, respectively. These findings demonstrate that lozenges containing red algae powder can be successfully produced with acceptable physical properties; however, improvement of raw material standardization or enrichment is required to enhance antioxidant efficacy.